PELATIHAN DIGITAL, PEMBUATAN WEBSITE DAN PENYULUHAN SWAMEDIKASI TENTANG PENYAKIT KULIT BAGI PELAJAR DI DUSUN KERSAN BANTUL - Bayu Setyo Aji; Hasna Isnaini Wijayanti; Vivia Nur Ramadhani; Yogi Tri Karunia; Nurani 'Aisyah Rahmasari; Ismi Musyaffangatul Ma'riffah; Rani Kurniawati; Siti Suhaibah; Lutfi Angga Dwi Cahya; Riski Fathur Rahman; Tri Rochmadi (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Community service through Real Work Lectures (KKN) is a form of student contribution and involvement in solving problems in the society. This study aims to utilize the knowledge obtained by raising awareness of digital development and improving health quality for the people of Kersan Village, Bantul Regency. The methods used in this study are observation, direct and indirect. The forms of student implications in this activity include digital marketing training for MSMEs, the creation of village websites, self-medication counseling about skin diseases, KKN-T students' involvement in post health activities and physical exercise. The results showed that through KKN activities, public awareness of digital development and improvement of health quality has increased. This is evidenced by the community's support and situation in participating in activities. In the presence of KKN activities, people can understand and implement digital marketing strategies to increase their competitiveness and business sustainability in the current digital era. In addition, people can maintain self-health and the environment and body fitness, which are efforts to improve the quality of life